Pendampingan Identifikasi Karakteristik Limbah dan Pengolahan Limbah Ternak di Desa Suka Damai Kecamatan Bulango Utara - Siswatiana R. Taha; Ismail Abdullah; Abdillah Ma'ruf Hadjim; Agung Prawira Sampe; Nezza Valerina; Zulfikri R.A. Djaapar (Universitas Negeri Gorontalo, 2026)
This community service aims to identify the characteristics of various types of waste based on the physical properties of livestock and slaughterhouse activities in Suka Damai Village, North Bulango District, Bone Bolango Regency, Gorontalo Province. The observational descriptive method was used to analyze the characteristics of waste including shape, color, odor, origin, and nature of waste. The identification results showed that livestock solid waste consists of livestock manure with different characteristics between types: cow manure with a water content of 75-85%, goat manure with a water content of 60-70%, and chicken manure mixed with urine with a high ammonia content. Liquid waste includes urine with a BOD of 2000-5000 mg/L and cage washing water, while slaughterhouse waste shows the most complex characteristics with blood (BOD up to 150,000-200,000 mg/L), rumen contents, and washing water with a COD of 4000-15000 mg/L. Identification of appropriate waste characteristics is crucial for determining appropriate waste management strategies to minimize environmental impacts and maximize the potential for resource utilization with sustainable principles. Integrated waste management based on its characteristics can minimize negative impacts, improve occupational health and safety, and provide added economic value for business actors.